Os fundidores de metal na Colômbia e no Brasil: um estudo transversal em Popayán e São Carlos no campo CTS - Enríquez, Maribel Deicy Villota (2017)
The present study aims to describe and characterize the transformations of the handcrafted crafts in metallurgy and goldsmithing in Popayán - Colombia and São Carlos - Brazil, through a transversal study in relation to the trade of the blacksmith and jeweler. It is an interdisciplinary study carried out in the perspective of social studies of science and technology (CTS). Adopting the descriptive methodology, combining techniques of the ethnographic and historical method, in particular the collaborative investigation. Procedures were adopted for documentary analysis: the history of life and the reflective interview for purposes of data collection and empirical research. Seven artisans of both sexes, aged between 38 and 70 years, living in Popayán - Colombia and São Carlos / SP, Brazil, were interviewed. All ethical procedures in human research were observed. To analyze the data, we focus on three axes: the change of the blacksmith and jeweler's office, the life histories of the participants and the characterization of the craft techniques from distant times until today. Considering the significant changes in the surroundings of the craft trades today, the construction of the new social relations of the environment and the artisans is identified and analyzed. The presence of the theme of aging is pointed out, being the craftsman a protagonist of the active aging, whose work carried out during the life is strongly influenced by the technical-technological transformations. Being a craftsman is a profession that takes itself in the continuity of time, but that today is losing the possibility of being transmitted.